Juridical Analysis of the Court Decision on the Contentious Marriage Validation Petition Case Number: 1817/Pdt.G/2025/PA.JB - M. Aslam Fadli (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The background of this study arises from the fact that unregistered marriages (nikah siri) are still prevalent in Indonesia, making marriage validation petitions an important legal instrument to obtain state recognition. However, in this case, a legal issue arose because the petitioner did not involve Mursani’s previous wives, who are still alive and have children that legally may have interests in the heir’s status and inheritance rights. The research questions in this study are as follows: 1) What are the judge’s juridical considerations in rejecting the marriage validation petition? 2) Have the judge’s considerations complied with the provisions of positive law and the substantive justice principles in Islamic law?. This study employs a normative juridical method using a case approach and a statute approach. Data sources are obtained from court decisions, legislation (Law No. 1 of 1974 on Marriage, the Compilation of Islamic Law, and Supreme Court Regulations related to family cases), as well as Islamic legal doctrines and literature. The analysis results show that the judge rejected the marriage validation petition because the first and second wives were not involved as respondents, even though they legally have potential interests in the outcome of the ruling. This consideration was based on the principle of audi et alteram partem (the right of every party to be heard), which is a fundamental principle of justice. However, substantively, this rejection creates a problem of legal utility, as it leaves the petitioner’s (third wife’s) marital status and her children’s legal standing unprotected, both administratively and civilly—particularly concerning inheritance and lineage rights. This study concludes that the judge’s decision is formally in accordance with the principles of civil procedural law; however, materially, it does not fully reflect the principles of utility and substantive justice for legally vulnerable parties, particularly for children born from unregistered marriages. A more progressive judicial guideline is needed so that judges can balance formal legal certainty with the protection of the civil rights of children and women in contentious marriage validation (isbat nikah) cases.